Experimental Study of the Wickless Heat Pipe Heat Exchanger by Using Nano Fluid - Osamah Raad Skheel; Nabil J. Yasin; Audai Hussain Al-abbas; Sumair Ahmed Soomro (Journal of Techniques)
The use of wickless heat pipe heat exchangers has been improving a wide range of thermal applications such as solar water heaters. Therefore, more scientific research needs to be conducted to improve its performance. In the present study, a wickless heat pipe heat exchanger test rig has been designed and fabricated to investigate the effect of different parameters on its performance. Two different heat pipe working fluids have been used namely pure water and water with nanoparticles (Al2O3) using different fluid volume ratios (20%,40%,60%,80%, and 100%). The concentrations of the nanoparticles in water range between 1.3 and 7 % wt. For the heat exchanger, various inlet hot air temperatures (50, 55, and 60 oC) have been tested at the hot side (heat pipe evaporator) whereas the inlet temperature of the cold side (heat pipe condenser) has been maintained at 20 oC. The effect of airflow Reynolds number has also been examined with a range of 2583-20664. Results showed that the best heat exchanger effectiveness is achieved at a Reynolds number of 10332 and nanoparticles concentration of 7% wt. Also, the use of nanoparticles reduced the thermal resistance in the heat pipe due to the significant reduction in its surface temperature compared to that of pure water.